PECULIARITIES OF REPLACEMENT ENZYME THERAPY IN CHILDREN WITH CYSTIC FIBROSIS: BENEFITS OF HIGH-TECH ENZYMES - O.I. Simonova; E.A. Roslavtseva (Вопросы современной педиатрии, 2011)
In the past years we have gained enormous success not only in the field of understanding of pathologic basis and genetics of cystic fibrosis, but we have also developed new therapeutic approach to this disease. Enzyme therapy is one of the main parts of a complex treatment of cystic fibrosis. Correct therapeutic decision upon medication and treatment regimen allows to reach dramatic amelioration o patient’s condition, and significantly decrease the risk of complications of the disease itself and side-effects of the treatment given. This article contains guidelines of enzyme therapy in cystic fibrosis and clinical mistakes analysis that occur while deciding upon therapy. Key words: chronic pancreatic failure, replacement enzyme therapy, kreon, cystic fibrosis, children. (Voprosy sovremennoi pediatrii — Current Pediatrics. — 2011; 10 (5): 152–156.)